Application of SMES Unit to improve the performance of doubly fed induction generator based WECS - Yunus, A. M. Shiddiq (Curtin University, 2012)
Due to the rising demand of energy over several decades, conventional energy resources have been continuously and drastically explored all around the world. As a result, global warming is inevitable due to the massive exhaust of CO2 into the atmosphere from the conventional energy sources. This global issue has become a high concern of industrial countries who are trying to reduce their emission production by increasing the utilization of renewable energies such as wind energy. Wind energy has become very attractive since the revolution of power electronics technology, which can be equipped with wind turbines. Wind energy can be optimally captured with wind turbine converters. However, these converters are very sensitive if connected with the grid as grid disturbances may have a catastrophic impact on the overall performance of the wind turbines.In this thesis, superconducting magnetic energy storage (SMES) is applied on wind energy conversion systems (WECSs) that are equipped with doubly fed induction generators (DFIGs) during the presence of voltage sags and swells in the grid side. Without SMES, certain levels of voltage sags and swells in the grid side may cause a critical operating condition that may require disconnection of WECS to the grid. This condition is mainly determined by the voltage profile at the point of common coupling (PCC), which is set up differently by concerned countries all over the world. This requirement is determined by the transmission system operator (TSO) in conjunction with the concerned government. The determined requirement is known as grid codes or fault ride through (FRT) capability.The selection of a SMES unit in this thesis is based on its advantages over other energy storage technologies. Compared to other energy storage options, the SMES unit is ranked first in terms of highest efficiency, which is 90-99%. The high efficiency of the SMES unit is achieved by its low power loss because electric currents in the coil encounter almost no resistance and there are no moving parts, which means no friction losses. Meanwhile, DFIG is selected because it is the most popular installed WECS over the world. In 2004 about 55% of the total installed WECS worldwide were equipped with DFIG. There are two main strategies that can be applied to meet the grid requirements of a particular TSO. The first strategy is development of new control techniques to fulfil the criterion of the TSOs. This strategy, however, is applicable only to the new WECS that have not been connected to the power grid. If new control techniques are applied to the existing gridconnected WECSs, they will not be cost effective because the obsolete design must be dismantled and re-installed to comply with current grid code requirements. The second strategy is the utilization of flexible AC transmission system (FACTS) devices or storage energy devices to meet the grid code requirements. This strategy seems more appropriate for implementation in the existing WECS-grid connection in order to comply with the current grid code requirements. By appropriate design, the devices might be more cost effective compared to the first strategy, particularly for the large wind farms that are already connected to the grid.A new control algorithm of a SMES unit, which is simple but still involves all the important parameters, is employed in this study. Using the hysteresis current control approach in conjunction with a fuzzy logic controller, the SMES unit successfully and effectively improves the performance of the DFIG during voltage sag and swell events in the grid side; thus, this will prevent the WECS equipped with DFIG from being disconnected from the grid according to the selected fault ride through used in this study. The dynamic study of DFIG with SMES during short load variation is carried out as an additional advantage of SMES application on a DFIG system. In this study, the proposed SMES unit is controlled to compensate the reduced transfer power of DFIG during the short load variation event. Moreover, the SMES unit is also engaged in absorbing/storing some amount of excessive power that might be transferred to the grid when the local loads are suddenly decreased. Finally, the studies of intermittent misfires and fire-through that take place within the converters of DFIG are carried out in order to investigate the impact of these converter faults on the performance of DFIG. In this part, the proposed SMES unit is controlled to effectively improve the DFIG’s performance in order to prevent it from being disconnected or shut down from the power grid during the occurrence of these intermittent switching faults.